Association of a polymorphism of the transforming growth factor-β1 gene with cerebral amyloid angiopathy. Issue 5 (15th April 2005) - Hamaguchi, T; Okino, S; Sodeyama, N; Itoh, Y; Takahashi, A; Otomo, E; Matsushita, M; Mizusawa, H; Yamada, M
Abstract : Background: A recent study showed that transforming growth factor-β1 (TGF-β1) induces amyloid-β deposition in cerebral blood vessels and meninges of a transgenic mouse model of Alzheimer's disease (AD), and that TGF-β1 mRNA levels are correlated with cerebral amyloid angiopathy (CAA) in human AD brains. A T/C polymorphism at codon 10 in exon 1 of the TGF-β1 gene has been reported to be associated with the serum TGF-β1 concentration. We investigated whether the TGF-β1 polymorphism is associated with the risk of CAA. Methods: The association between the severity of CAA and the T/C polymorphism at codon 10 in exon 1 of the TGF-β1 was investigated in 167 elderly Japanese autopsy cases, including 73 patients with AD. The apolipoprotein E ( APOE ) genotype was also determined. Results: The genotypes (TT/ TC/ CC) were associated with the severity of CAA significantly in all patients (p  =  0.0026), in non-AD patients (p  =  0.011), and APOE non-ε4 carriers (p  =  0.0099), but not in AD patients or APOE ε4 carriers. The number of the T alleles positively correlated with the severity of CAA in all patients (p  =  0.0011), non-AD patients (p  =  0.0026), and APOE non-ε4 carriers (p  =  0.0028), but not in AD patients or APOE ε4 carriers. The polymorphism was not significantly associated with AD. Conclusions: Our results suggest that the polymorphism in TGF-β1 is associated with the severity of CAA, especially in non-AD patients and APOE non-ε4 carriers.